TEKNIK PERANAN KITOSAN DALAM PENINGKATAN PERTUMBUHAN TOMAT (Lycopersicum esculentum) SELAMA FASE VEGETATIF - PIPIH SUPTIJAH; AGOES M. JACOB; SUGARA MURSID (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
Chitosan is product of shrimp shell waste utilization that derived from chitin. Based on its nature and characteristics, it is known that chitosan has important role in agriculture as a stimulant for the plant defense system as well as growth and production of some horticultural crops such as tomatoes. The purpose of this research is to study the influence of the chitosan treatment on the growth of tomatoes and to determine the effect of treatment combination on the growth of tomatoes. Chitosan treatment experiments on the growth of tomatoes during vegetative phase is done by Complete Random Design with 1 factor, that is chitosan treatments combination including P1 (control), P2 (chitosan soaking 25 ppm), P3 (watering and chitosan soaking 25 ppm), P4 (soaking and spraying chitosan 25 ppm) and P5 (soaking, watering and spraying chitosan 25 ppm). Chitosan soaking treatment at 25 ppm in tomato seeds have more value in growth rate and growth effort than the untreated plant. The best treatment is founded in the combination of soaking treatment with chitosan spraying in 25 ppm (P4), it’s better if it’s compared with other treatment (each parameter include the height of plants, the number of branches, the number of leaves, the length of leaves and wet weight and dry weight of the plants)